2017
DOI: 10.1111/cas.13284
|View full text |Cite
|
Sign up to set email alerts
|

Development of protein degradation inducers of oncogenic BCRABL protein by conjugation of ABL kinase inhibitors and IAP ligands

Abstract: Chromosomal translocation occurs in some cancer cells, which results in the expression of aberrant oncogenic fusion proteins that include BCR‐ABL in chronic myelogenous leukemia (CML). Inhibitors of ABL tyrosine kinase, such as imatinib and dasatinib, exhibit remarkable therapeutic effects, although emergence of drug resistance hampers the therapy during long‐term treatment. An alternative approach to treat CML is to downregulate the BCR‐ABL protein. We have devised a protein knockdown system by hybrid molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 42 publications
(46 reference statements)
4
60
0
Order By: Relevance
“…The modularity of our approach should enable the straightforward development of PHOTACs that target many other classes of proteins. For instance, existing PROTACs that target CDK4/6 (30), CDK9 (16), BTK (19,20), ABL (17,39), ALK (anaplastic lymphoma kinase) (40), MET (18), MDM2 (murine double minute 2) (41), and Tau (42) could be adapted to become light activatable. Our PHOTACs for BRD2,3,4 may enable new in sights into epigenetic pathways and potentially serve as precision tools in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The modularity of our approach should enable the straightforward development of PHOTACs that target many other classes of proteins. For instance, existing PROTACs that target CDK4/6 (30), CDK9 (16), BTK (19,20), ABL (17,39), ALK (anaplastic lymphoma kinase) (40), MET (18), MDM2 (murine double minute 2) (41), and Tau (42) could be adapted to become light activatable. Our PHOTACs for BRD2,3,4 may enable new in sights into epigenetic pathways and potentially serve as precision tools in medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering studies by the Crews lab have shown that BCR-ABL PROTACs, consisting of CRBN or VHL recruiters linked to BCR-ABL ATP binding pocket-targeting kinase inhibitors such as dasatinib and bosutinib or allosteric inhibitors such as GNF-2, showed preferential degradation of c-ABL over modest degradation of BCR-ABL (Burslem et al, 2019;Lai et al, 2016). Notably, this work has spurred development of various degradation strategies targeting BCR-ABL (Demizu et al, 2016;Shibata et al, 2017Shibata et al, , 2019Shimokawa et al, 2017;Zhao et al, 2019). In this study, we aimed to determine whether our recently discovered covalent RNF114 recruiter nimbolide could be used to kinase-targeting PROTACs, and if so, whether differential selectivity in degrading BCR-ABL, compared to similar BCR-ABL PROTACs employing VHL or CRBN could be attained.…”
Section: Main Textmentioning
confidence: 99%
“…As a proof-of-concept study, we designed and synthesized a series of hybrid molecules consisting of MeBS and all-trans retinoic acid, and found that they induced the proteasomal degradation of cellular retinoic acid binding protein-II. 18,19,21,29) Then, we developed various hybrid molecules by connecting tamoxifen, androgen receptor (AR) antagonists, and KHS-108 to MeBS, which induce the degradation of estrogen receptor (ER), 20,22) AR, 34) and transforming acidic coiled-coil containing protein 3, 23,27) respectively. In addition to these targets, HaloTag-fused proteins 24,26) and huntingtin 32) were successfully degraded by bestatin-based SNIPERs.…”
Section: Introductionmentioning
confidence: 99%